Structural Proteomics High-Throughput Methods - Owens, Raymond J.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Humana, 2015)
This updated and expanded volume reflects the current state of the structural protein field with improved and refined protocols that have been applied to particularly challenging proteins, notably integral membrane proteins and multi-protein complexes. Structural Proteomics: High-Throughput Methods, Second Edition begins by exploring the resources available for curation, annotation, and structure prediction in silico, and continues with methods for sample preparation of both proteins and crystals, as well as structural characterization techniques. Written for the highly successful Methods in Molecular Biology series, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls. Practical and up-to-date, Structural Proteomics: High-Throughput Methods, Second Edition will aid researchers in expanding our knowledge of this vital and expansive area of protein science.
Protein Structure Annotation Resources -- PiMS: A Data Management System for Structural Proteomics -- Prediction and Analysis of Intrinsically Disordered Proteins -- I-TASSER Suite: A Standalone Package for Protein Structure Prediction and Structure-Based Protein Function Annotation -- Characterization and Production of Protein Complexes by Co-Expression in Escherichia coli -- The Production of Multi-Protein Complexes in Insect Cells Using the Baculovirus Expression System -- Production of Cell Surface and Secreted Glycoproteins in Mammalian Cells -- Cell-Free Protein Synthesis Systems Derived from Cultured Mammalian Cells -- Crystallization: Digging into the Past to Learn Lessons for the Future -- Screening of Stable G Protein-Coupled Receptor Variants in Saccharomyces cerevisiae -- Cell-Free Expression of G Protein-Coupled Receptors -- GFP-Based Expression Screening of Membrane Proteins in Insect Cells Using the Baculovirus System -- Methods for the Successful Crystallization of Membrane Proteins -- Application of In Situ Diffraction in High-Throughput Structure Determination Platforms -- CD Spectroscopy: An Essential Tool for Quality Control of Protein Folding -- High Throughput Studies of Protein Shapes and Interactions by Synchrotron Small-Angle X-Ray Scattering -- Automated Structure Determination from NMR Spectra -- Solid State Nuclear Magnetic Resonance Spectroscopy for Membrane Protein Structure Determination -- Native Mass Spectrometry: Towards High-Throughput Structural Proteomics.
Keywords: Proteins .; Protein Science; Protein Structure